Kritik terhadap Unsur Tafsir Ad-Dakhĭl: : Studi atas Penafsiran Ibn ‘Uṡaimin terhadap Q.S. Al- Al-Māidah (5): 64 - Mukhtar, Ahmad Syahrul (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
The study of Qur’anic exegesis is generally divided into two categories: interpretations considered sound (al-aṣĭl) and ṡose regarded as deviant (ad-dakhĭl). Every exegete’s work inevitably reflects this distinction. This study aims to investigates al-‘Uṡaymĭn’s interpretation of Surah al-Mā’idah verse 64 in Aḥkām min al-Qur'ān al-Karĭm. In interpreting this verse, he does not employ ta’wĭl (figurative reinterpretation). Instead, he prioritizes a textual reading, avoiding taḥrĭf (distortion of meaning), ta‘ṭĭl (negation), takyĭf (describing ṡe modality of God’s attributes), tamṡĭl (likeness), or tashbĭh (anṡropomorphism). Al-‘Uṡaymĭn is a follower of the teachings of Muḥammad ibn ‘Abd al-Wahhāb (Wahhabism). Within Wahhabi doctrine, the use of rational interpretation for the mutashābihāt (ambiguous verses) is generally rejected. This research employs a descriptive qualitative method with theory of al-dakhĭl and al-aṣĭl to investigates the validity of his interpretation. This study found that al-Uṡaimin’s interpretation on al-Maidah: 64 indicates as deviant (al-dakhĭl). This is due to his rejection of ta’wĭl and the influence of Wahhabism, which tends to promote literalism and is associated with tajsĭm, tashbĭh, takyĭf, and tamṡĭl. His interpretation relies too rigidly on the outward literal meaning while dismissing the direct use of reason in interpreting ambiguous verses.